2019
DOI: 10.3390/catal9050440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Random Mutagenesis and In Vivo Selection on the Specificity and Stability of a Thermozyme

Abstract: Factors that give enzymes stability, activity, and substrate recognition result from the combination of few weak molecular interactions, which can be difficult to study through rational protein engineering approaches. We used irrational random mutagenesis and in vivo selection to test if a β-glycosidase from the thermoacidophile Saccharolobus solfataricus (Ssβ-gly) could complement an Escherichia coli strain unable to grow on lactose. The triple mutant of Ssβ-gly (S26L, P171L, and A235V) was more active than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In addition to rational approaches, also random mutagenesis studies involving suitable in vivo selection mechanisms were conducted with hyperthermozymes. One study focusing on the β-glycosidase from Saccharolobus solfataricus showed that mutations far from the active site may have crucial impact on the enzyme's activity and stability profiles [132]. While a mutant with three random mutations showed a twofold enhanced specific activity towards galactosides at 85 °C, the higher flexibility of the enzyme variant that enabled this increase in substrate turnover also led to an almost 300-fold reduced thermal stability.…”
Section: Protein Engineering To Tailor Plant-degrading Enzymes For Inmentioning
confidence: 99%
“…In addition to rational approaches, also random mutagenesis studies involving suitable in vivo selection mechanisms were conducted with hyperthermozymes. One study focusing on the β-glycosidase from Saccharolobus solfataricus showed that mutations far from the active site may have crucial impact on the enzyme's activity and stability profiles [132]. While a mutant with three random mutations showed a twofold enhanced specific activity towards galactosides at 85 °C, the higher flexibility of the enzyme variant that enabled this increase in substrate turnover also led to an almost 300-fold reduced thermal stability.…”
Section: Protein Engineering To Tailor Plant-degrading Enzymes For Inmentioning
confidence: 99%
“…The authors studied the well-defined outer ring of the substrate groove of a non-specific nuclease from Pseudomonas syringae and defined it as a potential target for modulation of the enzymatic performance. Perugino et al [15] demonstrated that random mutagenesis and biological selection allowed the identification of residues that are critical in determining thermal activity, stability and substrate recognition of a β-glycosidase from the thermoacidophile Saccharolobus solfataricus. Cyclodextrin transferase's product specificity was changed finally by Sonnendecker et al [16] by semi-rational mutagenesis, obtaining larger cyclodextrin's rings of up to 12 units.…”
mentioning
confidence: 99%